2018
DOI: 10.1111/obes.12237
|View full text |Cite
|
Sign up to set email alerts
|

From the Cradle to the Grave: The Influence of Family Background on the Career Path of Italian Men

Abstract: Using a longitudinal data set that contains detailed information on working histories of Italian men, we investigate the relationship between parental background and sons’ earnings profiles. We find that the parental influence on sons’ earnings persists over the career and that the direct influence controlling for sons’ education is large and grows during the working career. After twenty years of experience, our baseline specification indicates that an additional year of parental education is associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
(67 reference statements)
3
5
0
Order By: Relevance
“…Previous studies reported similar observations in Japan, Iran, and Germany [ 19 , 22 , 25 ]. These findings agree with studies showing the family’s influence on career choices [ 23 , 26 ] which may be expected since most students live with their families when deciding on their careers [ 27 ]. Increasing parental awareness and student career options may mitigate ill-informed decisions regarding choosing dentistry as a future career.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies reported similar observations in Japan, Iran, and Germany [ 19 , 22 , 25 ]. These findings agree with studies showing the family’s influence on career choices [ 23 , 26 ] which may be expected since most students live with their families when deciding on their careers [ 27 ]. Increasing parental awareness and student career options may mitigate ill-informed decisions regarding choosing dentistry as a future career.…”
Section: Discussionsupporting
confidence: 91%
“…This may be because the students at that age are financially dependent on their families and most respondents were females for whom the financial motives may be of less concern in the Libyan society. In previous studies, women were more motivated by flexible working hours and altruism than men, indicating that financial freedom and self-employment were primary motives for studying dentistry [22][23][24]. In this study, males were more likely to be motivated by prestige and working in the healthcare field.…”
Section: Discussionsupporting
confidence: 44%
“…We focus on the employment trajectories of Italian women who transitioned from school to work between late 1970s and early 1990s. Different cohorts were differently exposed to labour market deregulation, but the ‘access’ to a stable employment trajectory remained associated with individual characteristics and parental background (Raitano & Vona, 2018 ; Struffolino & Raitano, 2020 ). Besides the structural constraints discouraging women—and particularly mothers—from participating in the labour market (e.g., lack of accessible childcare, residual parental leave for fathers, persistent wage gaps), maternal employment has proved to be a driver of women’s employment and intergenerational mobility, over and above parental education.…”
Section: Illustrative Applicationmentioning
confidence: 99%
“…Parents play a vital role in every aspect of their children's lives including their career choice (Michele & Francesco, 2018). Besides, Kumazhege (2017) also found there is a significant relationship between parents and career choices.…”
Section: Parents or Guardiansmentioning
confidence: 99%